Strategi Pembelajaran Ppkn Dalam Menumbuhkan Sikap Toleransi Antar Umat Beragama Di Sekolah Menengah - Nurlailah (CV. SINAR HOWUHOWU, 2025)
This study aims to identify effective teaching strategies in Civics Education (PPKn) for fostering religious tolerance among secondary school students. The research adopts a qualitative approach, utilizing interviews, observations, and document analysis techniques. The results indicate that teaching strategies based on discussions, collaborative projects, and case studies are effective in building tolerance among students. The role of teachers as facilitators, guiding open discussions on religious diversity, also plays a significant role in creating an inclusive learning environment. However, challenges related to stereotypes and prejudices outside the school environment still need further attention. The study concludes that Civics Education, which emphasizes tolerance values, can produce more inclusive students who appreciate differences, but continuous support from all stakeholders is necessary.